High-Yield Production of Catalytically Active Regulatory [NiFe]-Hydrogenase From Cupriavidus necator in Escherichia coli - Fan, Qin; Caserta, Giorgio; Lorent, Christian; Zebger, Ingo; Neubauer, Peter; Lenz, Oliver; Gimpel, Matthias (Frontiers in Microbiology, 2022)
Hydrogenases are metalloenzymes catalysing the reversible hydrogen conversion into protons and electrons. Here, especially the [NiFe] hydrogenases from Ralstonia eutropha are interesting due to their oxygen tolerance. However, a heterologous production strategy is required to overcome the low production yields in their native host to meet the demands for biotechnological applications and scientific research. Previously, we used the regulatory hydrogenase (RH) from R. eutropha as a model for the development of a heterologous hydrogenase production process in E. coli. Although high yields could be obtained, the enzyme produced was inactive due to the lack of the [NiFe] cofactor. In the present study, we improved the production process in order to obtain an active RH. We investigated important factors such as cultivation mode, metal addition, production temperature and time as well as the co-expression of specific native maturase genes. The RH was successfully matured by co-over-expression of native hyp genes from R. eutropha in E. coli as confirmed by in vitro activity measurements and spectroscopic investigations. Finally, the improved growth conditions enabled a high-yield production of about 80 mg L-1 of active RH and achieved up to 160-fold space-time active yield in E. coli compared to that determined in native R. eutropha (˂ 0.1 U (L d)-1). Overall, the strategy developed here provides useful tools for further biotechnological production of functional hydrogenases. In particular, the strategy can be applied in scale-up studies to achieve the economical production of complex metalloenzymes that are difficult to express.